PENGARUH KESEMPATAN INVESTASI, RATING OBLIGASI TERHADAP BIAYA UTANG DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di BEI) - Lila Nurcahyanti; Haryetti Haryetti; Akhmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study is motivated by many inconsistencies of previous research and the lack of related research conducted on the non financial sector. This study aims to analyze the influence of invesment opportunity set (IOS), bond rating, and on the cost of debt (COD) with firm size as anmoderating variable. Moderation regression analysis (MRA) was used to analyze data. Using 50 sample of mining firms listed in Indonesia Stock Exchange from 2012-2015. The sampel in this study were selected using purposive sampling, the method of analysis used in this study is multiple moderating regression by using SPSS version 22.0 as the sottware for processing data. The result showed that IOS had a negative and significant impact toward COD, bond rating had a negative and not significant impact toward COD, and firm size had a positive and not significant impact toward COD,firms size is able moderate the influence of IOS and COD and firm size did not influence of bond rating and COD.Keywords :Investment Opportunity Set, Bond Rating, Firm Size, Cost Of Debt, Firm Performance, and MVBE.